Review of Greenberg R. & Hamilakis Y., Archaeology, Nation, and Race: Confronting the Past, Decolonizing the Future in Greece and Israel. - Gori, Maja (Ex Novo: Journal of Archaeology, 2024)
Review of Greenberg R. & Hamilakis Y., Archaeology, Nation, and Race: Confronting the Past, Decolonizing the Future in Greece and Israel. Cambridge: Cambridge University Press, 2022 - DOI: 10.1017/9781009160247